The effect of mathematics communication ability on students' learning achievement in year five - Sintawati, Mukti; Dwita, Metti (Universitas Ahmad Dahlan, 2022)
This study aims to determine the effect of mathematics communication skills on student achievement in grade V Public Elementary School 08 and 10 District Gantung. This study uses a quantitative research approach with ex-post facto research. The population in this study were 58 students of class V Public Elementary School 08 and 10 District Gantung, with a sample of 45 people. Mathematics communication skills (Variable X) and mathematics learning achievement were the variables investigated (Variable Y). This study's data collection method employs tests that have been validated and proven to be reliable. The SPSS version 21 program is used for hypothesis testing, which employs simple linear regression analysis and Pearson correlation. The study's results, obtained using a simple linear regression test and a Pearson correlation test, show that mathematics communication ability has a significant effect on students' mathematics learning achievement, as indicated by a sig less than 0.005, which is equal to 0.000 with the simple linear regression equation Y = - 2,219 + 0,980. Pearson Correlation is obtained for 0.0802, indicating that the pearson correlation is strongly correlated when viewed through the guidelines for the degree of relationship. Based on this, it is possible to conclude that mathematics communication skills have a strong correlation with students' mathematics learning achievement.